The Written Text in Conceptual Art (An Analytical Study) (Al-Academy, 2023)
The tagged research problem (the outputs of the written text in conceptual art) dealt with a comparative analytical study in the concept of conceptual art trends (land art - body art - art - language).The study consisted of four chapters. The first chapter dealt with the theoretical framework, which was represented in presenting (the research problem), which raised the following question: What is the role of the written text in the transformations of the conceptual arts?The first chapter included (the importance of research) and (research objectives) seeking to conduct comparative research in the written text within the trends of conceptual art as a moving phenomenon in art, and to reveal the variable written text in the trends of conceptual art. As for the limits of the research, it focused on studying the concept of the written text in the works of conceptual art trends and their outputs, by analyzing their illustrated works from the period 2002-2013 in Europe and America. The chapter also included (defining terms) The second chapter: which is represented by the theoretical framework, contains two topics: The second chapter: which is represented by the theoretical framework, contains two topics:The first topic: an introduction to the concept of writing in the visual field. Conceptual art also dealt with the cognitive and artistic root. As for the second topic, it included: the written text in conceptual artThe third chapter (procedural framework): is concerned with research procedures, defining the research community and selecting the research sample from it, the number of which is (5) models, from the directions of conceptual art, then the research tool and sample analysis.The fourth chapter: includes the results of the analysis of samples for each direction, then the results of the comparative analysis, conclusions, recommendations and proposals, and a list of sources and translation of the research summary in English.